Pulmonary Nodule Volumetry at Different Low Computed Tomography Radiation Dose Levels With Hybrid and Model-Based Iterative Reconstruction: A Within Patient Analysis. Issue 4 (July 2016) - den Harder, Annemarie M.; Willemink, Martin J.; van Hamersvelt, Robbert W.; Vonken, Evertjan P.A.; Schilham, Arnold M.R.; Lammers, Jan-Willem J.; Luijk, Bart; Budde, Ricardo P.J.; Leiner, Tim; de Jong, Pim A.
Abstract : Objective: The aim of the study was to determine the effects of dose reduction and iterative reconstruction (IR) on pulmonary nodule volumetry. Methods: In this prospective study, 25 patients scheduled for follow-up of pulmonary nodules were included. Computed tomography acquisitions were acquired at 4 dose levels with a median of 2.1, 1.2, 0.8, and 0.6 mSv. Data were reconstructed with filtered back projection (FBP), hybrid IR, and model-based IR. Volumetry was performed using semiautomatic software. Results: At the highest dose level, more than 91% (34/37) of the nodules could be segmented, and at the lowest dose level, this was more than 83%. Thirty-three nodules were included for further analysis. Filtered back projection and hybrid IR did not lead to significant differences, whereas model-based IR resulted in lower volume measurements with a maximum difference of −11% compared with FBP at routine dose. Conclusions: Pulmonary nodule volumetry can be accurately performed at a submillisievert dose with both FBP and hybrid IR.